Rural tourism in line with green and technological development: EU perspectives - Dimitrijević, Miloš (Hotel and Tourism Management, 2025)
Purpose – Considering the need to diversify activities in the EU rural areas, as well as significant greenhouse gas emissions from tourism, this paper aims to examine the importance of sustainable rural tourism based on green and smart technologies for the economic development of the EU. Methodology – OLS panel regression was used to examine the impact of rural tourism and the factors that contribute to its development on the economic development of the EU. The development of rural tourism compared to urban tourism in the EU was evaluated using the Mann-Whitney U test, while the Friedman test was used to monitor the trend of rural tourism in the period 2012-2023. Findings – Rural tourism and the factors that contribute to its development, such as internet users and employment in rural areas, have a positive impact on the economic development of the EU, while greenhouse gas emissions have a negative impact. Rural tourism is more developed than tourism in urban areas, but only in recent years has it reached its pre-pandemic level of development. Implications – Important EU strategic documents dealing with rural development, such as the LEADER program, the EU Green Deal, the EU Common Agricultural Policy and the European Strategy should implement the recommendations related to rural tourism development in line with smart, sustainable and inclusive growth.